2007
DOI: 10.1002/bdd.542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute renal failure on the pharmacokinetics of telithromycin in rats: negligible effects of increase in CYP3A1 on the metabolism of telithromycin

Abstract: It was reported that the expression of CYP3A1 increased in rats with acute renal failure induced by uranyl nitrate (rat model of U-ARF) compared with controls. It was shown that telithromycin was mainly metabolized via CYP3A1/2 in rats in this study. Hence, the pharmacokinetic parameters of telithromycin were compared after both intravenous and oral administration at a dose of 50 mg/kg to control rats and a rat model of U-ARF. After intravenous administration of telithromycin to rats with U-ARF, the AUC and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The clearance, the volume of distribution, the half-life, the plasma protein binding, the urinary excretion, and the extent of absolute oral bioavailability (F) of telithromycin in humans are 12-16 ml/min/kg, 2.1-4.5 l/kg, 7-23 h, 70%, 19-27% of the dose, and 41-112%, respectively (4)(5)(6). Recently, Lee and Lee (7) reported that telithromycin is primarily metabolized via hepatic microsomal cytochrome P450 (CYP) 3A1/2 in male Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…The clearance, the volume of distribution, the half-life, the plasma protein binding, the urinary excretion, and the extent of absolute oral bioavailability (F) of telithromycin in humans are 12-16 ml/min/kg, 2.1-4.5 l/kg, 7-23 h, 70%, 19-27% of the dose, and 41-112%, respectively (4)(5)(6). Recently, Lee and Lee (7) reported that telithromycin is primarily metabolized via hepatic microsomal cytochrome P450 (CYP) 3A1/2 in male Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact values of hepatic and intestinal first-pass effects were not measured separately in NARs, the total percentages of both first-pass effects were supposed to be increased in NARs and this could result in a smaller F in NARs. Similarly, it has been also reported that hepatic and intestinal first-pass effects of several drugs were subjected to significant changes in various disease states in accordance with their specific CYP isozyme changes [33,34].…”
Section: Discussionmentioning
confidence: 79%
“…The lower CL NR might result from a decrease in the expression of hepatic CYP3A (Fig. 1) in ECLPS rats, because telithromycin was metabolized via CYP3A1/2 in rats (15). Decreased expression of rat hepatic 3A2 has also been reported (24,25).…”
Section: Figmentioning
confidence: 80%
“…After centrifugation of the blood sample, a 100-l aliquot of plasma sample was stored at Ϫ70°C until it was used for the HPLC analysis of telithromycin. The preparation and handling of urine samples and gastrointestinal tract samples (including contents of the tract and feces) taken at 24 h were similar to reported methods (14,15).…”
Section: Treatment With Eclpsmentioning
confidence: 92%
See 1 more Smart Citation